2020
DOI: 10.3390/genes11080914
|View full text |Cite
|
Sign up to set email alerts
|

Using Micro- and Macro-Level Network Metrics Unveils Top Communicative Gene Modules in Psoriasis

Abstract: (1) Background: Psoriasis is a multifactorial chronic inflammatory disorder of the skin, with significant morbidity, characterized by hyperproliferation of the epidermis. Even though psoriasis’ etiology is not fully understood, it is believed to be multifactorial, with numerous key components. (2) Methods: In order to cast light on the complex molecular interactions in psoriasis vulgaris at both protein–protein interactions and transcriptomics levels, we studied a set of microarray gene expression analyses con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…There is growing interest in microarray platforms as a way to detect genetic alterations and to determine biomarkers for many diseases 10 . Several biomarkers and pathways have been implicated in the development of psoriasis in previous studies on microarray data 11,12 , but still no studies focus on the link between ferroptosis and psoriasis. In this study, we compared the gene expression of patients with psoriasis arthritis or psoriasis and normal person by integrated bioinformatics methods.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing interest in microarray platforms as a way to detect genetic alterations and to determine biomarkers for many diseases 10 . Several biomarkers and pathways have been implicated in the development of psoriasis in previous studies on microarray data 11,12 , but still no studies focus on the link between ferroptosis and psoriasis. In this study, we compared the gene expression of patients with psoriasis arthritis or psoriasis and normal person by integrated bioinformatics methods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we propose the hypothesis that association analysis between hub genes contributed to PsA development and ferroptosis regulators may provide a new perspective on the pathogenesis of high cancer risk in patients with PsA.There is growing interest in microarray platforms as a way to detect genetic alterations and to determine biomarkers for many diseases 13 . Several biomarkers and pathways have been implicated in the development of PsD in previous studies on microarray data 14,15 . Moreover, genetic and proteomic studies also confirmed the overlap and differences between PsC and PsA.…”
mentioning
confidence: 99%
“…There is growing interest in microarray platforms as a way to detect genetic alterations and to determine biomarkers for many diseases 13 . Several biomarkers and pathways have been implicated in the development of PsD in previous studies on microarray data 14,15 . Moreover, genetic and proteomic studies also confirmed the overlap and differences between PsC and PsA.…”
mentioning
confidence: 99%
“…Cho et al described two polymorphisms in GPR174 and ITM2A genes on the X chromosome that might be associated with autoimmune thyroid diseases (AITDs) in Korean children [ 1 ]. Naderi et al identified 17 potential genes proven to be pivotal in psoriasis for therapeutic/diagnostics purposes in that pathology [ 2 ].…”
mentioning
confidence: 99%